The Biomarkers for Predicting Viral HepatitisAssociated Hepatocellular Carcinoma - Yang, Qing; Sun, Changfeng; Sheng, Yunjian; Chen, Wen; Deng, Cunliang (Turkish Journal of Gastroenterology, 2022)
Background: Hepatocellular carcinoma (HCC) is the fifth most common cancer in the world, and more than half of the newly diagnosedcases are chronic hepatitis B patients. Due to the lack of specific clinical manifestations, many patients are already at an advancedstage at the time of diagnosis and therefore have missed the best time for treatment. Organs in a pathological state usually secretespecific substances into the blood, which can indirectly indicate the pathological state of the organ, so some biological markers in theblood can be used as a tool to predict the incidence of HCC.Methods: The Research articles related to HCC were collected by searching PubMed databases with the keywords “hepatocellularcarcinoma”, “serum biomarker”, “hepatitis B”, “prediction” and “prognosis”, and Additional articles were identified by manual search ofreferences found in the primary articles, followed by a summary and review.Results: Viral hepatitis is the main cause of HCC worldwide, and this phenomenon is particularly prominent in Asian and African populations. A variety of serological markers including M2BPGi, IL-6 and COMP can be used to predict the incidence of long-term HCC inpatients. The risk of HCC is dynamic rather than constant, and dynamic detection will help improve prediction accuracy. For hepatitisB patients, HBV DNA load and HBcr Ag are important predictive markers of HCC.Conclusion: For a high-risk population of HCC, early risk prediction is helpful to guide clinical work, and timely adjustments of thescreening frequency and treatment plan are helpful to prolong the survival time of HCC patients.